Можливість застосування реверсивного механізму сплати ПДВ в Україні - Стадник, М.В. (Економіка промисловості, 2015)
Розглянуто особливості реверсивного механізму сплати ПДВ в ЄС, зокрема перелік операцій, до яких країни-члени можуть за власним бажанням застосовувати даний механізм. Визначено окремі сектори економіки України, у яких можливе використання реверсивного механізму сплати ПДВ, а також наведено аргументи щодо даного вибору з урахуванням рівня тінізації та прибутковості кожного сектору. Рассмотрены особенности реверсивного механизма уплаты НДС в ЕС, в частности перечень операций, к которым страны-члены могут по собственному желанию применять данный механизм. Определены отдельные секторы экономики Украины, в которых возможно использование реверсивного механизма уплаты НДС, а также приведены аргументы по данному выбору с учетом уровня тенизации и прибыльности каждого сектора. The EU VAT system is notably characterized by fractionized payments, and VAT being collected at each stage of the production and distribution chain after off-setting the input VAT paid on purchases against the output VAT received on sales. However, this system has also led to the risk of “missing trader” fraud, where the supplier evades paying to the State the VAT collected on sales while the customer has the right to deduct VAT on the basis of a valid tax invoice. A way to tackle such a fraud is the application of a so-called “reverse charge mechanism”, where the customer becomes liable for the VAT on goods or services supplied to him. In this case, the customer is paying and deducting the VAT via the same VAT return (within the limit of its VAT deduction right), thus eliminating the cash risk as no actual payment of the VAT takes place. The following international trends led to researching of applicability of reverse charge mechanism within the Ukrainian VAT system. After analyzing the shadow economy in separate sectors and examining their level of profitability it was singled out the list of operations that may use reverse charge mechanism of VAT, namely supply of: mobile telephones, game consoles, tablet PCs and laptops; used material, used material which cannot be re-used in the same state, scrap; agricultural products (may not only cereals and industrial crops including oil seeds and sugar beet); construction work. However, the list of these sectors is not exhaustive. Thus, the perspectives of further research may be as follows: studying of possibilities of adaptation of the mechanism to national realities; analyzing of the economic situation of each sector, which are presented in Directive 2006/112/EC, in Ukraine. Such further studies will enhance the reliability of the information and confirm the economic efficiency of any changes of current tax legislation of Ukraine.